Implementation of Augmented Reality Learning Media Technology at the Primary and Secondary Education Levels in Cimahi City, West Java - Nur Alamsyah; Dina Fauziyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
Currently the development of technology is progressing very rapidly and its development cannot be stopped. With so many advanced technologies that have emerged, various kinds of human work can be done in more innovative ways. One example is in the field of education. Currently, there are various kinds of technology-based learning media, one of which is learning media using Augmented Reality technology or often shortened to AR. Application Development as Learning Media to Build Space for Elementary/Junior High School Level Using Marker Augmented Reality Method is one form of utilizing AR technology in the field of education, especially as a learning medium. With the creation of this Augmented Reality-based learning media for building space, It is hoped that students can understand learning materials easily, and students' interest in learning can increase because the objects in the space are designed to be attractive, colorful, and interactive to avoid boredom. Based on this, this research is one of the new breakthroughs in the world of education that utilizes technological advances and helps teachers provide more interesting learning media. Meanwhile, the results of this study are in the form of an AR application and a mathematical book (module). this research is one of the new breakthroughs in the world of education that utilizes technological advances and helps teachers provide more interesting learning media. Meanwhile, the results of this study are in the form of an AR application and a mathematical book (module). this research is one of the new breakthroughs in the world of education that utilizes technological advances and helps teachers provide more interesting learning media. Meanwhile, the results of this study are in the form of an AR application and a mathematical book (module).